PRIMER REGISTRO DE NEMATODOS MERMITHIDAE, PARÁSITOS DE PROCALUS MUTANS Y PROCALUS REDUPLICATUS (CHRYSOMELIDAE: ALTICINAE) - Jerez, Viviane; Centella, Cristian (Acta Entomológica Chilena, 2022)
Preadult stages of one species of nematode Mermithidae were found for the first time parasitizing adults of chrysomelid insects, Procalus m utans and Procalus recluplicatus, two sympatric and syntopic species found in the VIII región of Chile. A comparison of parasitism between both host species was made. Valúes of interspecific frequency were not significantly different (0.35 < P < 0.40). The average infection number was 20.0% for P. mutans and 10.4% for P. reduplicatus, and no relationship with the sex of the host was established (P. mutans: 0.65 < P < 0.70; P. reduplicatus: (0.75 < P < 0.80). It is supposed that the inoculation of larval nematodes could proceed in the soil, whilst the third larval stage construct a pupal cell.